Rabiscando ensino de Ciências em quadrinhos para aprendizagem de estudantes imigrantes venezuelanos - Carvalho, Kennyson dos Santos (2022)
Teaching Science is not a simple action. It becomes even more complex when there are foreign subjects in the class of students who do not have command of the Portuguese language. This situation became even more common with the mass arrival of Venezuelan immigrants to the city of Manaus, which made the number of students of this nationality enrolled in the state basic education network grow exponentially. Faced with this difficulty, it is up to the teacher to make use of resources that can make the learning of these students more fruitful. In this context, comics represent a relevant alternative for the explanation of phenomena and concepts in a more dynamic way. The general objective of the study was to analyze how the comic book becomes an important pedagogical resource for the teaching and learning of Venezuelan immigrant students about the preservation of the creeks of Manaus. The methodological procedures included bibliographic and exploratory research, with a qualitative approach, with the phenomenological perspective being the structuring axis of the study. A comic book was created whose central theme is the preservation of the creeks of Manaus. The plot has three characters: a) Iara: a 12- year-old man from Manaus; b) Vó Naiara: retired teacher and grandmother of Iara, and; c) Pablo, a young Venezuelan classmate of Iara's. The dialogues present in the story, as well as the plot developed can trigger debates on the theme of pollution, thus stimulating the participation of students in their training itinerary. In this way, the use of comics in science teaching represents a valid alternative to make the explanation of concepts relevant to this field of knowledge less tiring and more attractive for students. The study concluded that the teaching of Science to Venezuelan immigrants through comics is a viable solution, whose usefulness is not restricted only to the delivery of content, but also to the engagement of these students in causes that directly influence their quality of education. life. Thus, comics can not only be seen as a relevant didactic resource, but also a way of teaching values and diligent attitudes towards the preservation of the environment and, therefore, the construction of a better and fairer world to live in. to live. Keywords: Venezuelan immigrants. Science teaching. Manaus creeks. Comic Book.